Multimodality imaging in the evaluation of left ventricle myocardial deformation determined by edema and scar in acute myocarditis. (4th February 2022) - Angelini, G; Bonanni, M; Paiocchi, VL; Leo, LA; Schlossbauer, S; Pasotti, E; Pedrazzini, G; Valgimigli, M; Favale, S; Forleo, C; Pavon, AG; Faletra, F
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: acute myocarditis (aMY) is characterized by the presence of edema and myocardial scar detected by cardiovascular magnetic resonance (CMR).  Aim of our study is to investigate the diagnostic value of two-dimensional (2D) speckle tracking echocardiography and Cardiovascular Magnetic Resonance (CMR) feature tracking (FT) in detecting edema and myocardial scar in aMY. METHODS: all consecutive patients with clinically suspected aMY were enrolled in our study. Inclusion criteria were: 1) new ECG abnormalities 2) myocardial cytolysis markers and 3) absence of angiographically detectable coronary artery disease. Exclusion criteria included poor cine image quality caused by respiratory motion and arrhythmia. All patients underwent transthoracic echocardiography and cardiac function was evaluated by a comprehensive assessment of LV function, including 2D speckle-tracking echocardiography (2D STE). CMR was performed in all patients in a 3T scanner. Extension of edema and myocardial scar were respectively evaluated on T2 mapping and on Late Gadolinium Enhancement sequences considering numbers of segments involved according to 17-segment model (AHA). FT analysis of the left ventricle (LV) was performed using the Tissue Tracking Module to obtain LV strain data. RESULTS: 52 patients were included in the study, mean age was 36± 17 years, three patients were female (6%). Mean LVEF was 56, 2 ± 7, 2 % and mean end diastolic volume index (EDVi) was 62, 52 ± 19, 02 ml/m2. 10 patients (19, 2%) had impaired EF with mean values of 44, 6 ± 6, 15%. aMY was confirmed in all patients with the presence of myocardial edema and subepicardial late gadolinium enhancement (LGE).  Inferior segments were involved in 28 patients (53, 8%), lateral segment in 19 patients (36, 5%), septal segments in 7 patients (13, 5%)  and anterior segments in 15 patients (28, 8%). 2D STE LV GLS was -16.41± 5, 47% while CMR-FT LV GLS was -19, 07 ± 4, 65%, showing a good agreement between the two methods (r = 0, 5; p < 0, 001). The univariate analysis showed a significant correlation between 2D STE LV GLS and CMR-FT LV GLS with the extension of myocardial edema assessed by CMR (r= 0, 43; p= 0, 002 and r = 0.47; p = 0, 002 respectively). The univariate analysis did not show a significant correlation between 2D STE LV and the extension of myocardial scar assessed by CMR (r= 0.2; p= 0.155) while a significant correlation was found between CMR-FT LV GLS and myocardial scar (r = 0.4; p = 0.01). CONCLUSIONS: in patients with aMY, good correlation was found between CMR-FT and 2D STE in the evaluation of GLS. 2D STE LV GLS and CMR-FT LV GLS proved to have a good correlation with the extension of myocardial edema, while only CMR-FT LV GLS proved to be associated with myocardial scar extension.